Determination of Domoic Acid in Plankton Net Samples from Golden Horn Estuary, Turkey, Using HPLC with Fluorescence Detection - YURDUN, TÜRKAN (SPRINGER, 2018)
This study focused on the fluctuations of domoic acid (DA) levels in plankton net samples collected from the Golden Horn Estuary (GHE), Turkey, between August 2011 and July 2012. DA concentrations were determined by high-performance liquid chromatography (HPLC), using a fluorenylmethoxycarbonyl (FMOC) derivatization technique. Monthly and biweekly data were evaluated with environmental variables, and their influence on DA production is discussed. DA levels in plankton net samples varied between 0.36 and 94.34 A mu g L- 1. DA levels showed remarkable seasonal variation and they were generally higher in May, 2012, but no DA was detected between February and April, 2012. DA production was mostly controlled by temperature, with nitrate and silicate limitations being secondary factors that influenced DA concentrations.
Keywords: Domoic acid; Pseudo-nitzschia; Golden Horn Estuary; HPLC-FLD analysis; PERFORMANCE LIQUID-CHROMATOGRAPHY; DIATOM NITZSCHIA-PUNGENS; PSEUDO-NITZSCHIA; SEA; BACILLARIOPHYCEAE; SHELLFISH; MARMARA; BAY; PHYTOPLANKTON; DYNAMICS